STANDARTS AND DYNAMICS IN SPORTS WEBSITES ONLINE EDITING - Efrem Karanfilov (Scientific Publishing House. NSA Press, 2019)
This text covers theoretical and practical problems of the sport's editor work in the conditions of media convergence. It provides analysis of issues, such as the trustworthiness of journalistic sources, the use of the social networks, the editor's new functions and responsibilities. Another approach is the tendency for emphasizing more on the visualization as a message, which reveals completely new influence over the perception of the information and its influence for mind shaping among the society. The methods of research are based on content analyses, comparative analyses and historical review. The main researched objects are the technology of editing and framing the information in the modern media. The text combines theoretical knowledge and description of typical practical solutions, which editors may wish to apply in their day-to-day work. The main importance is given to presenting the rules and practices which combine the journalistic principles and the requirements of the technologies, which are challenging the personality of the journalists to have a wider and deeper all round preparation both in the humanitarian area and in the specific aspects of sport competition, and second - the operation skills, taking into consideration the modern aesthetical and technological tendencies in the media based on Internet communications. The research is based on the keys of media journalism in Bulgaria and selected media from Europe and USA from the recent years. It is the first investigation in the field of online editing in the sports media in Bulgaria and will serve as a guideline for further scientific research. It is also considered to be informative for the methodical practical preparation of sports journalists.